2010
DOI: 10.1063/1.3447374
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of p-type and n-type doped inverse silicon opals - towards optically amplified silicon solar cells

Abstract: While the silicon photonic crystals have promised revolutionary developments in the field of optical telecommunications and optical computing, it has only recently been realized that their prowess to trap and slow photons could potentially and significantly improve the efficiency of silicon solar cells. In this work n-doped and p-doped inverse silicon opals are synthesized and processed to optimize their electrical charge transport properties, which are shown to be of semiconductor device quality. Moreover a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Takashi's group demonstrated that the inverse crystalline Si opal (abbreviated as i‐cSi‐o), with its three‐dimensional open structure, has a comparable electrical conductivity to bulk crystalline Si. In addition, such a structure can effectively trap light via slow photons and/or prolong life time of minority charge carriers through inhibition of their recombination by the omnidirectional photonic bandgap . In another work, the authors evaluated the spectral response for the electrical properties of i‐cSi‐o with 600 nm and 280 nm sphere diameter templates and observed a slow photon enhanced photoconductivity ( Figure ).…”
Section: The Slow‐photon Effect In Photonic Crystals For Solar‐energymentioning
confidence: 99%
“…Takashi's group demonstrated that the inverse crystalline Si opal (abbreviated as i‐cSi‐o), with its three‐dimensional open structure, has a comparable electrical conductivity to bulk crystalline Si. In addition, such a structure can effectively trap light via slow photons and/or prolong life time of minority charge carriers through inhibition of their recombination by the omnidirectional photonic bandgap . In another work, the authors evaluated the spectral response for the electrical properties of i‐cSi‐o with 600 nm and 280 nm sphere diameter templates and observed a slow photon enhanced photoconductivity ( Figure ).…”
Section: The Slow‐photon Effect In Photonic Crystals For Solar‐energymentioning
confidence: 99%
“…Furthermore, even if the surfaces of the PC can be sufficiently passivated, electron scattering from these surfaces will reduce carrier mobility and increase the series resistance in the cell. 30 Deterred charge transport and increased recombination losses will weaken the validity of the assumption that each photon absorbed in the μc-Si:H cell generates and contributes one electron to the output current. However, in this initial study we have neglected the electrical transport issues associated with the inverted μc-Si:H opal and have upheld this assumption in order to fairly compare the optical behaviour of the four micromorph cells considered herein.…”
Section: The μC-si:h Cell Within the Micromorph Structured In The Formentioning
confidence: 98%
“…Conductive inverted opals from silicon, ZnO, and Al-doped ZnO were fabricated by chemical vapor deposition (CVD) and atomic layer deposition (ALD) using silica or polymer opals as templates [70,88,89]. Thus, photonic structures could be integrated directly in silicon solar cells [90,91]. The combination of self-assembling monodisperse colloids and replication of the resulting opals with vapor deposition methods enables the fabrication of reflection layers with relative ease especially on large substrates.…”
Section: Self-organizing Photonic Crystalsmentioning
confidence: 99%